Kenya : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2003)
This selected issues paper assesses Kenya's revenue performance, the labor market, and the health of the banking sector. It analyzes Kenya's revenue potential, tax system, and economic activity while increasing revenues; assesses the labor market; and also notes the nonperforming loans (NPLs) in the Kenyan banking sector, especially in public sector banks, and suggests structural measures to reduce cost pressures in the banking sector, lower the NPLs, and reduce the spread between lending and deposit interest rates. It also provides the detailed statistical appendix of Kenya.